2007
DOI: 10.1115/1.2736704
|View full text |Cite
|
Sign up to set email alerts
|

A Low Friction Bearing Based on Liquid Slip at the Wall

Abstract: In recent years it has been shown experimentally by a number of workers that simple, Newtonian liquids can slip against solid surfaces when the latter are both very smooth and lyophobic. It has also been shown theoretically how, based on a half-wetted bearing principle, this phenomenon may be used to significantly reduce friction in lubricated sliding contacts and thus make possible the hydrodynamic lubrication of very low load contacts. This paper describes the experimental validation of this concept. A low l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 27 publications
4
79
0
1
Order By: Relevance
“…Furthermore, many authors have concluded that for solid-liquid slip to take place, the surfaces have to be very smooth, generally below 6 nm RMS [12,41,42,50]. However, the present authors have presented an investigation in which friction reduction with DLC coatings was measured [7] in full film EHL even when the combined RMS roughness of the surfaces was in the range of 155-355 nm.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Furthermore, many authors have concluded that for solid-liquid slip to take place, the surfaces have to be very smooth, generally below 6 nm RMS [12,41,42,50]. However, the present authors have presented an investigation in which friction reduction with DLC coatings was measured [7] in full film EHL even when the combined RMS roughness of the surfaces was in the range of 155-355 nm.…”
Section: Introductionmentioning
confidence: 69%
“…However, it is more uncertain if the friction reduction achieved with the coatings compared to the uncoated reference is only due to thermal insulation, or if a smaller part of the friction reduction is also due to solid-liquid slip. The influence of surface roughness on solid-liquid slip has been discussed by several authors, where many of them have concluded that for slip to occur, the surfaces have to be very smooth [12,39,41,42,49], typically 6-12 nm RMS. The critical roughness is most likely depending on the size of the molecules of the liquid used [24,36,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F + =0.037), the minimum value is achieved when HD = 0.25 in full slip condition. Slip can be used to reduce friction under full film, hydrodynamic lubrication Choo et al [1]. …”
Section: Mathematical Model and Its Solutionmentioning
confidence: 99%
“…The sliding step bearing is one example of texturing, leading to a high load support. Regarding slip, Choo et al [1] showed that liquid slip could be used to considerably reduce friction under full film, hydrodynamic lubrication. Tauviqirrahman et al [2] demonstrated that partial texturing gave even better results than full texturing.…”
Section: Introductionmentioning
confidence: 99%